Graph-analytic engineering method of corrosion current calculation in multielectrode system; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Mozilov А. I.; Ivanov G. V.; Safroshkina L. D.; Demin Yu. V. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа